30. RECURRENT AND/OR PERSISTENT WHEEZING IN CHILDREN UNDER 5 YEARS OLD AT THE RESPIRATORY DEPARTMENT - NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine the causes of recurrent and/or persistent wheezing in children under 5 years old treated at the Respiratory Department - Nghe An Obstetrics and Pediatrics Hospital.Methods: There was a cross-sectional study in 86 patients under 5 years old who had recurrent and/or persistent wheezing symptoms admitted at the Respiratory Department - Nghe An Obstetrics and Pediatrics Hospital from March 2024 to September 2024.Results: Persistent wheezing after viral infection and airway abnormalities were the two most common causes of recurrent and/or persistent wheezing, in which bronchiolitis was mainly seen in children under 12 months with an early-onset wheezing phenotype. The number of wheezing episodes of the 3 wheezing phenotypes was different. The late-onset wheezing phenotype was usually recurrent wheezing and diagnosed asthma. The clinical and paraclinical symptoms at the time of admission vary according to the causes of wheezing.Conclusions: Persistent wheezing after viral infection is the most common cause of recurrent and/or persistent wheezing in children younger than 5 years of age, and the age of wheezing onset is valuable for determine the causes of wheezing.
Keywords: Wheezing; recurrent; persistent; children under 5 years old